Sewa Menyewa Dalam Perspektif Ekonomi Islam - Ali Ridlo (Mukaddimah: Jurnal Studi Islam, 2022)
Abstract The purpose of this study is to describe how leasing in the perspective of Islamic economics. The research method used is qualitative research with a literature study approach. This research is limited and carried out from January 2021 to November 2021.The results showed that the pelungguh rental in Padukuhan Seneng, Siraman Village, Wonosari District, Gunungkidul Regency, Yogyakarta Special Region Province was carried out by the head of the hamlet as the recipient of the pelungguh who rented out (Mu’jir) and the community as tenants (Mus’ta’jir). While the governor’s Regulation number 34 of 2017 concerning the utilization of Village Land, the lease is carried out by the Village Government, the proceeds of which are given to the Village Government and Village Apparatus receiving the pelungguh. Economically, there is income obtained from the rent for the Village Government and Village Apparatus who receive Pelungguh. Meanwhile, according to Imam Syafi’i, renting is the same as buying and selling. The item being rented must be his. Although the pelungguh does not belong to the village apparatus, based on the Governor’s Regulation Number 34 of 2017, the leasing of the pelungguh is allowed, and the one who rents it is the Village Government. The rental of pelunguh by the head of the hamlet is a problem that occurs in the Village Government. Keywords: Rent, Tenants, Renters, Pelungguh, Islamic economics